2019
DOI: 10.1111/tid.13216
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of fulminant Clostridioides difficile infection with emergent fecal microbiota transplantation in a patient with acute myeloid leukemia and prolonged, severe neutropenia

Abstract: We present a patient with acute myeloid leukemia and prolonged, severe neutropenia who developed fulminant Clostridioides difficile infection refractory to medical therapy and was high‐risk for surgical intervention. He was treated with fecal microbiota transplantation (FMT) for life‐saving cure. The patient had subsequent clinical improvement, however, developed multidrug‐resistant Pseudomonas aeruginosa bacteremia 2 days post‐procedure. We describe subsequent investigation of this event that found this bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Helicobacter pylori has been classified as a carcinogen since 1994, although gastric cancer appears in the gastric mucosa epithelium, several observations suggest that the cancer cells may originate from circulating bone marrow stem cells recruited to the mucosa to replace normal gastric stem cells that have underwent apoptosis due to Helicobacter pylori infection [29]. Matthwe S. L. Lee et al reported that a patient with AML and prolonged severe neutropenia was successfully treated with emergent fecal microbiota transplantation (FMT) due to Clostridioides difficile infection [31]. Kazuhiko Kakihana et al indicated that FMT might shift the systemic allogeneic immune response to an anti-inflammatory state by changing the intestinal microbiota and might be effective against other forms of acute graft-versus-host disease [32], all of which suggested that FMT might be a promising and safe therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori has been classified as a carcinogen since 1994, although gastric cancer appears in the gastric mucosa epithelium, several observations suggest that the cancer cells may originate from circulating bone marrow stem cells recruited to the mucosa to replace normal gastric stem cells that have underwent apoptosis due to Helicobacter pylori infection [29]. Matthwe S. L. Lee et al reported that a patient with AML and prolonged severe neutropenia was successfully treated with emergent fecal microbiota transplantation (FMT) due to Clostridioides difficile infection [31]. Kazuhiko Kakihana et al indicated that FMT might shift the systemic allogeneic immune response to an anti-inflammatory state by changing the intestinal microbiota and might be effective against other forms of acute graft-versus-host disease [32], all of which suggested that FMT might be a promising and safe therapy.…”
Section: Discussionmentioning
confidence: 99%
“…AFMT treatment was considered to limit the risk of such complications by promoting a return to non-disturbed intestinal microbiota. Nevertheless, there is limited clinical evidence to date on FMT e ciency in patients suffering from ALM and treated with antibiotics [37].…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompromised hosts, safety issues, especially disseminated bacterial infections in neutropenic hosts, are of concern. To date, data on efficacy and safety of FMT for rCDI in haematologic malignancy and HSCT are limited to small case series and case reports [100][101][102][103][104][105]. A case report that led to an FDA national alert and mandated additional screening for those conducting FMT research under FDA supervision described a patient in a trial of FMT after allogenic HSCT (NCT03720392), who died from severe neutropenic sepsis secondary extended-spectrum beta-lactamase (ESBL) E. coli.…”
Section: Primary and Secondary Prevention Methodsmentioning
confidence: 99%